PROSPECTS AND STRATEGIES FOR DEVELOPING GAMBIR (UNCARIA GAMBIR ROXB.) IN PAKPAK BHARAT DISTRICT - Marino Manik; Surtan Hasibuan; Nelva Meyriani Br Ginting (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Gambier ( Uncaria gambir Roxb. ) is a valuable plantation commodity with the potential to be developed as a source of income for communities in various regions in Indonesia. Pakpak Bharat Regency has agro-climatic conditions that are relatively suitable for gambier cultivation, but its development is not yet optimal in terms of production, marketing, and farmer institutions. This study aims to analyze the existing conditions of gambier cultivation, identify agronomic and socio-economic factors that influence its development, and formulate prospects and strategies for gambier development in Pakpak Bharat Regency. The research method uses a descriptive approach with data collection through field observations, interviews, and documentation studies, as well as a SWOT analysis to determine development strategies. The results show that Pakpak Bharat has considerable potential in terms of land suitability, labor availability, and increasing market opportunities. However, there are still obstacles in the form of low product quality, limited processing technology, and weak market access. The SWOT analysis shows that development strategies can be directed at improving farmer capabilities, modernizing processing, strengthening institutions, and expanding marketing networks. Thus, gambier plants have good development prospects in Pakpak Bharat Regency if supported by appropriate policies and technical interventions.